A Combined Theoretical and Photoelectron Spectroscopy Study of Al3Hn− (n=1–9) clusters. Issue 18 (21st August 2021) - Xu, Jing; Zhang, Xinxing; Wang, Haopeng; Fu, Lijuan; Li, Xiang; Grubisic, Andrej; Harris, Rachel M.; Eichhorn, Bryan; Gantefoer, Gerd; Ding, Yihong; Kiran, Boggavarapu; Kandalam, Anil K.; et al.
Abstract: Combined photoelectron spectroscopic experiments and computational studies have been performed on Al3 H n − ( n =1–9) clusters. Three modes of hydrogen bonding to the Al3 moiety have been observed: terminal, bridging, and capping. Among various hydrides, Al3 H5 − and Al3 H8 − clusters have highest HOMO‐LUMO gap and largest electron affinity, respectively. Our studies indicate that as the number of hydrogen atoms increase the presence of AlH2 groups, representing the tetrahedral coordination of the Al atom, which in turn led to the stoichiometric ring structure. Abstract :